2014
DOI: 10.3168/jds.2014-8247
|View full text |Cite
|
Sign up to set email alerts
|

A gas chromatography-mass spectrometry-based metabolomic approach for the characterization of goat milk compared with cow milk

Abstract: In this work, the polar metabolite pool of commercial caprine milk was studied by gas chromatography-mass spectrometry and multivariate statistical data analysis. Experimental data were compared with those of cow milk and the discriminant analysis correctly classified milk. By the same means, differences due to heat treatments (UHT or pasteurization) on milk samples were also investigated. Results of the 2 discriminant analyses were combined, with the aim of finding the discriminant metabolites unique for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 22 publications
1
60
0
Order By: Relevance
“…GC/MS data analysis was conducted by integrating each resolved chromatogram peak. Identification of metabolites was performed using the standard NIST08 mass spectra library, a library developed at the Max Planck Institute of Golm, and, when available, by comparison with authentic standards (Scano et al, 2014).…”
Section: Gc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…GC/MS data analysis was conducted by integrating each resolved chromatogram peak. Identification of metabolites was performed using the standard NIST08 mass spectra library, a library developed at the Max Planck Institute of Golm, and, when available, by comparison with authentic standards (Scano et al, 2014).…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Among different approaches, metabolomics is an effective way to characterise and to verify the authenticity of food products, being based on identification and quantification of characteristic metabolites through the application of MVA to data originating from different analytical techniques (Cevallos-Cevallos, Reyes-De-Corcuera, Etxeberria, Danyluk, & Rodrick, 2009;Marincola et al, 2012;Piras et al, 2013;Scano, Murgia, Pirisi, & Caboni, 2014). Metabolomics is able to identify a molecular fingerprint that accurately represents the food product, in all its aspects, and can discriminate from different or fraudulent varieties (Lindon, Nicholson, & Holmes, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To find the metabolites uniquely shared by the milk of a horse, Jersey cow, camel, yak, goat, caprine, buffalo and dairy cow, studies were carried out using NMR, LC-MS, or GC-MS methods [108,109]. These studies have indicated the following: (1) glycine and valine are only present in the milk of goats, malic acid and talose are only present in the milk of cows, and hydroxyglutaric acid is only present in pasteurized milk [108]; (2) both fructose and glucose exist in ultra-high temperature-treated milk or cow milk [108]; and (3) succinic acid and choline can be indicators to differentiate cow milk from the milk from a horse, Jersey cow, camel, yak, goat, caprine, or buffalo [109]. These results validated that metabolomics is a feasible approach for milk typology analysis to reduce food fraud [108,110].…”
Section: Metabolomics In Lactation Researchmentioning
confidence: 99%
“…These studies have indicated the following: (1) glycine and valine are only present in the milk of goats, malic acid and talose are only present in the milk of cows, and hydroxyglutaric acid is only present in pasteurized milk [108]; (2) both fructose and glucose exist in ultra-high temperature-treated milk or cow milk [108]; and (3) succinic acid and choline can be indicators to differentiate cow milk from the milk from a horse, Jersey cow, camel, yak, goat, caprine, or buffalo [109]. These results validated that metabolomics is a feasible approach for milk typology analysis to reduce food fraud [108,110]. Therefore, these metabolites, generated in response to various conditions in milk, are good biomarkers in the evaluation of milk quality and safety (summarized in Table 5).…”
Section: Metabolomics In Lactation Researchmentioning
confidence: 99%
“…The amount of lactose in bovine and goat milk is similar, but Alpha-s1 casein (only present in ruminant milk) is found in much lower concentrations in goat compared to bovine milk (Jenness, 1980;Park and Haenlein, 2008). Goat milk contains higher concentrations of nucleotides, polyamines and some of the essential amino acids (Ceballos et al, 2009;Scano et al, 2014). Goat, bovine and human milk also contain non-nutritional components, such as oligosaccharides, in different concentrations and structures that possible play a role in the different effects seem from formula-feeding.…”
Section: Introductionmentioning
confidence: 96%